Lateral Root Primordium Morphogenesis in Angiosperms - Torres-Martínez, Héctor H.; Rodríguez-Alonso, Gustavo; Shishkova, Svetlana; Dubrovsky, Joseph G. (Frontiers in Plant Science, 2019)
Morphogenetic processes are the basis of new organ formation. Lateral roots (LRs) are building blocks of the root system. After LR initiation and before LR emergence, a new LR primordium (LRP) forms. During this period, the organization and functionality of the prospective LR is defined. Thus, proper LRP morphogenesis is a decisive process during root system formation. Most current studies on LRP morphogenesis have been performed in the model species Arabidopsis thaliana; little is known about this process in other angiosperms. To understand LRP morphogenesis from a wider perspective, we review both contemporary and earlier studies. The latter are largely forgotten, and we made an attempt to integrate them into the present-day research. Particularly, we consider in detail the parent root tissue participation in LRP formation, cell proliferation and timing during LRP morphogenesis, and the hormonal and genetic regulation of LRP morphogenesis. Cell type identity acquisition and new stem cell establishement during LRP morphogenesis are also considered. Within each of these facets, unanswered or poorly understood questions are identified to help define the future research in the field. Finally, we discuss emerging research avenues and new technologies that could be used to answer the remaining questions in studies of LRP morphogenesis.